Exponential Trajectory Tracking Control of Nonholonomic Wheeled Mobile Robots - Plamen Petrov; Ivan Kralov (Mathematics)
Trajectory tracking control is important in order to realize autonomous driving of mobile robots. From a control standpoint, trajectory tracking can be stated as the problem of stabilizing a tracking error system that describes both position and orientation errors of the mobile robot with respect to a time-parameterized path. In this paper, we address the problem for the trajectory tracking of nonholonomic wheeled mobile robots, and an exponential trajectory tracking controller is designed. The stability analysis is concerned with studying the local exponential stability property of a cascade system, provided that two isolated subsystems are exponentially stable and under certain bound conditions for the interconnection term. A theoretical stability analysis of the dynamic behaviors of the closed-loop system is provided based on the Lyapunov stability theory, and an exponential stability result is proven. An explicit estimate of the set of feasible initial conditions for the error variables is determined. Simulation results for verification of the proposed tracking controller under different operating conditions are given. The obtained results show that the problem of trajectory tracking control of nonholonomic wheeled mobile robots is solved over a large class of reference trajectories with fast convergence and good transient performance.